Current progress of functional nanobiosensors for potential tuberculosis diagnosis: The novel way for TB control? - Yang, Xuran; Fan, Shuhao; Ma, Yuhe; Chen, Hui; Xu, Jun-Fa; Pi, Jiang; Wang, Wandang; Chen, Guanghui (Frontiers in Bioengineering and Biotechnology, 2022)
Tuberculosis (TB), induced by Mycobacterium tuberculosis (Mtb), is still one of the top killers worldwide among infectious diseases. Although several antibiotics have been developed to significantly relieve the TB epidemics worldwide, there are still several important scientific challenges for TB. As one of the most important issues in TB control, the diagnosis of TB is critical for the timely therapy of TB and thus responsible for the effective control of drug-resistant TB. Current TB diagnostic methods in clinic are still facing the difficulties that they can’t provide the rapid diagnostic results with high sensitivity and accuracy, which therefore requires the development of more effective novel diagnostic strategies. In recent decades, nanomaterials have been proved to show promising potentials for novel nanobiosensor construction based on their outstanding physical, chemical and biological properties. Taking these promising advantages, nanomaterial-based biosensors show the potential to allow the rapid, sensitive and accurate TB diagnosis. Here, aiming to increase the development of more effective TB diagnostic strategy, we summarized the current progress of nanobiosensors for potential TB diagnosis application. We discussed the different kind diagnostic targets for TB diagnosis based on nanobiosensors, ranging from the detection of bacterial components from Mtb, such as DNA and proteins, to the host immunological responses, such as specific cytokine production, and to the direct whole cell detection of Mtb. This work is expected to promote the future research on nanobiosensor-based TB diagnosis and finally benefit the more effective control of TB epidemic.